Stoichiometry Control for the Tuning of Grain Passivation and Domain Distribution in Green Quasi‐2D Metal Halide Perovskite Films and Light‐Emitting Diodes. (29th April 2020) - Cheng, Tai; Qin, Chuanjiang; Watanabe, Satoru; Matsushima, Toshinori; Adachi, Chihaya
Abstract: Quasi‐2D metal halide perovskite films are promising for efficient light‐emitting diodes (LEDs), because of their efficient radiative recombination and suppressed trap‐assisted quenching compared with pure 3D perovskites. However, because of the multidomain polycrystalline nature of solution‐processed quasi‐2D perovskite films, the composition engineering always impacts the emitting properties with complicated mechanisms. Here, defect passivation and domain distribution of quasi‐2D perovskite films prepared with various precursor compositions are systematically studied. As a result, in perovskite films prepared from stoichiometric quasi‐2D precursor compositions, large organic ammonium cations function well as passivators. In comparison, precursor compositions of simply adding large organic halide salt into a 3D perovskite precursor ensure not only the defect passivation but also the effective formation of quasi‐2D perovskite domains, avoiding unfavorable appearance of low‐order domains. Quasi‐2D perovskite films fabricated with a well‐designed precursor composition achieve a high photoluminescence quantum yield of 95.3% and an external quantum efficiency of 14.7% in LEDs. Abstract : Quasi‐2D perovskites are engineered in terms of defect passivation and exciton confinement to reach high emitting efficiency. Compared with preparing the precursor solution with stoichiometric quasi‐2D compositions, simply adding a large organic halide salt into the 3D perovskite precursor ensures not only defect passivation but also effective formation of quasi‐2D perovskite domains, avoiding unfavorable appearance of low‐order domains.